2017
DOI: 10.1002/dc.23752
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic neoplasms to the pancreas diagnosed by fine‐needle aspiration/biopsy cytology: A 15‐year retrospective analysis

Abstract: Cytologic diagnosis of metastasis to the pancreas is rare in our institution, comprising only 2.5% and 7.2% of total and malignant pancreatic FNA/CNB, respectively. FNA/CNB with ROSE proved to be an effective diagnostic modality, thereby obviating the need for more invasive procedures in the setting of pancreatic metastases. EUS-FNA was equally effective as CT-guided biopsies in achieving specimen adequacy and definitive diagnoses. We also present the first known case of a metastatic olfactory neuroblastoma to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Regarding neoplasm location, pancreatic head/neck was the most common location for metastasis in this study and other studies [ 4 , 10 ]. RCC is the most common primary tumor in PMET reported in literature, although some studies have described that lung cancer is the most common one [ 4 , 7 , 8 , 11 - 13 ]. This might be due to the tendency for hematogenous spread in RCC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding neoplasm location, pancreatic head/neck was the most common location for metastasis in this study and other studies [ 4 , 10 ]. RCC is the most common primary tumor in PMET reported in literature, although some studies have described that lung cancer is the most common one [ 4 , 7 , 8 , 11 - 13 ]. This might be due to the tendency for hematogenous spread in RCC [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of 4955 adult autopsy cases in the same study, there were 190 cases of pancreatic tumors, none with MCC. Raymond et al 16 reported a single case of MCC among 221 patients who were diagnosed with a pancreatic malignancy via FNA/core needle biopsy. Primary pancreatic neoplasm is an important differential for MCC metastatic to pancreas, especially with isolated pancreatic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic metastatic accounted for 0.9%-2.5% of EUS-FNA samples of the pancreas and 4.7%-7.2% of pancreatic malignancies[ 27 - 29 ]. These figures may be higher than those of other modalities because lesions with typical findings of pancreatic adenocarcinoma may be resected without EUS-FNA.…”
Section: Diagonsismentioning
confidence: 99%